Mimesis of Contrast in Shakespeare's Ephemeral Subplot and its Use in Victorian and Modernist Literature - Jiménez Hernando, Antonio (Journal of English Studies, 2024)
The aim of this paper is to present an overview of Shakespeare’s employment of a narrative technique that could be referred to as the “mimesis of contrast.” By analysing the characteristics of certain sequences in Macbeth, Henry IV 1 and The Tempest, it will be spelt out that Shakespeare’s sudden subplots, generally considered mere comic reliefs, are in fact revealing instances that not only mirror the play’s primary narrative but also succeed in generating a drastic poetic effect. Moreover, the use of this method will be considered in the works of Victorian and Modernist authors, notably Charles Dickens, James Joyce and T. S. Eliot. Lastly, the ideas of traditional Shakespearian critics like S. T. Coleridge and Thomas De Quincey shall work as central arguments in this article, aiding to conclude that Renaissance drama, and in particular Shakespeare’s motif of contrast, made an impact in the literature of the nineteenth and twentieth centuries.